Fixing the Public Hospital System in China - World Bank (Washington, DC, 2017)
In recent years, Chinese health care has improved rapidly, especially in the areas of equity and accessibility of services, as well as the movement toward universal coverage. A new round of health care reform, which was announced in April 2009, began implementation in 2010, with reform pilots in 16 urban areas. This paper analyzes a key pillar of this ongoing reform process, public hospital management. First, the paper reviews the history of public hospital reform, discusses hospital functions and responsibilities, and describes the structure and supply of health services. Second, it describes the main policy issues facing public hospitals, including financing sources and the hospital market environment. Third, it examines organizational arrangements in public hospitals, focusing on decision rights and governance. Fourth, the paper offers an international perspective and framework for assessing hospital reform. Finally, it summarizes the main policy issues and suggests next steps for policy reform. The paper draws on recent publications, grey literature, media reports, and interviews with key stakeholders.